Savor the danger - Foster, Lori, 1958- (Foster, Lori, 1958- Men who walk the edge of honor., 2011)
When hot-blooded mercenary Jackson Savor and Alani Rivers wake up next to each other, with no memory of how they got there, they race against time to find the truth even though it places their lives--and their newfound passion for each other--in danger.